One Century of regional Press in Costa Rica. A preliminary approach (1850-1950) - Quesada Rivera, Eugenio (2019)
The purpose of this article is to analyze the newspapers that circulated in the Costa Rican provinces between 1850 and 1950. With the postulates of the historians Jean-François Botrel and Robert Darnton, this article pretends to deepen our understanding of said newspapers, as well as the production and distribution processes. In conclusion, the educative reform occurred on 1886 fueled the raise of new provincial capitals, also the issuing of these papers was on its majority made in an artisan way and that the central politics model that Costa Rica opted for limited deeply the life cycle of these publications.